The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1981-863720150001000042957
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of different bracket bonding materials to the enamel subjected to thermal cycling

Abstract: ObjectiveThe aim of this study was to evaluate in vitro the shear bond strength of metallic orthodontic brackets to enamel using different bonding materials followed by thermal cycling. Methods A fluid composite resin (Transbond XT / 3M Unitek) and a resin-modified glass ionomer (Fuji Results No difference on shear bond strength was observed regarding the number of thermal cycles for each specimen (p = 0.873). A significant difference was found in shear bond strength between the bonding materials (p = 0.022)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Although previous studies have not evaluated the influence of cumulative intraoral stresses on brackets’ debonding values and ARIs, the effects of both thermocycling and cyclic fatigue loading had been separately tested in previous in-vitro studies, but often yielded contradicting findings. Ribeiro-Neto et al 19 and Rosolen et al 20 found no effect of thermocycling on bracket bonding strengths, and found that enamel damage was likely to occur during debonding when etch-and-rinse primer was utilized to bond composite adhesives to enamel. Elekdag-Turk et al 21 recorded no effect of thermocycling on bonding strengths after using etch-and rinse primers, although they found a significant reduction in bracket bonding strength to enamel when self-etch primer was used.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have not evaluated the influence of cumulative intraoral stresses on brackets’ debonding values and ARIs, the effects of both thermocycling and cyclic fatigue loading had been separately tested in previous in-vitro studies, but often yielded contradicting findings. Ribeiro-Neto et al 19 and Rosolen et al 20 found no effect of thermocycling on bracket bonding strengths, and found that enamel damage was likely to occur during debonding when etch-and-rinse primer was utilized to bond composite adhesives to enamel. Elekdag-Turk et al 21 recorded no effect of thermocycling on bonding strengths after using etch-and rinse primers, although they found a significant reduction in bracket bonding strength to enamel when self-etch primer was used.…”
Section: Discussionmentioning
confidence: 99%